Uji Akurasi Hasil Pengukuran Arah Kiblat Pegawai Kemasjidan Kua Menggunakan Aplikasi Google Earth - Iyan Hasjun; Andi Jusran Kasim; Nur Astaman Putra (Astroislamica: Journal of Islamic Astronomy, 2024)
This research aims to analyze the accuracy of qibla direction measurements conducted by mosque employees in the Limboro District, Polewali Mandar Regency, using the Google Earth application. The research method employed is descriptive field research with sociological, normative Islamic, and astronomical approaches. Data was collected through direct measurements by mosque employees using qibla compass tools combined with smartphone compass applications. Subsequently, the qibla direction of mosques and musala was evaluated using the Google Earth application. The research findings indicate that out of 12 mosques and 1 musala sampled, only 3 mosques have accurate qibla directions consistent with the measurements. Meanwhile, the other 9 mosques and 1 musala show significant deviations in qibla direction. These deviations point toward countries such as Yemen, Nigeria, Tanzania, Kenya, and Egypt, with variations ranging from 2° to 27°. The implications of this research can be used to enhance qibla direction measurement methods to align with Islamic Sharia regulations.